Some Remarks about Going Towards Inconsistencies - Décio Krause (Principia: An International Journal of Epistemology)
Inconsistencies! What do they mean? Can we support them? With this paper, we hope to contribute to the claim that we can tolerate inconsistencies in certain situations even without considering any logic that may enable us to do that, say some paraconsistent logic. We argue that in many cases where we apply reason we work in domains where inconsistencies appear and even so we neither get them out (but ‘support’ them) nor modify the underlying logic (such as classical logic) to avoid logical troubles. To make things more precise, we distinguish between inconsistency, anomaly, and contradiction. Our thesis is that we can reason sensibly even with classical logic in the presence of inconsistencies once (as we explain) we either ‘do not go there’ or make things so that the inconsistencies cannot be joined to arrive at a contradiction. Some sample cases are given to motivate the discussion.